ANALISIS IMPLEMENTASI KEBIJAKAN PROGRAM SENEMBAS DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARO - Della Crystine Sembiring; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study is motivated by the suboptimal level of marriage registration and ownership of marriage certificates in Karo Regency, despite the implementation of the SENEMBAS program as a public service innovation. This condition indicates a gap between policy design and its implementation in practice. This research applies George C. Edwards III’s policy implementation theory, which emphasizes four key variables: communication, resources, implementers’ disposition, and bureaucratic structure. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. The findings reveal that the implementation of the SENEMBAS program has not been fully effective. The communication aspect faces challenges due to uneven information dissemination and limited public understanding. In terms of resources, there are constraints in both the quantity and capacity of personnel, as well as geographical accessibility. The implementers’ disposition varies in terms of commitment, while the bureaucratic structure has not fully supported effective inter-unit coordination. In conclusion, the success of the SENEMBAS program implementation is highly dependent on the integration of these four factors. Therefore, strengthening policy communication, enhancing resource capacity, and optimizing institutional coordination are necessary to improve service effectiveness.